Emotional IQ - Goleman, Daniel (American Broadcasting Companies, 2008)
Daniel Goleman, author of Emotional intelligence, discusses the importance of emotional development in children. He explains how learning to delay gratification, read the feelings of others and manage anger can contribute to a successful life, perhaps even more than intelligence